Does hepcidin play a role in the pathogenesis of aphthae in Behcet's disease and recurrent aphthous stomatitis? - Cicek, D.; Dagli, A. F.; Aydin, S.; Dogan, F. Baskaya; Dertlioglu, S. B.; Ucak, H.; Demir, B. (Wiley, 2014)
BackgroundAphthae constitute one of the major signs in Behcet's disease (BD) and recurrent aphthous stomatitis (RAS). No scientific study has yet explored the relationship of hepcidins, which have antimicrobial effects, with RAS and BD. ObjectivesIn this study, we aimed to evaluate by immunohistochemistry whether hepcidin is synthesized by the salivary glands and to measure levels of prohepcidin and hepcidin (an antibacterial peptide) in the serum and saliva of patients with BD and RAS. MethodsThe study included 25 BD patients and 30 RAS patients, as well as a control group comprising 25 healthy individuals. Serum and saliva samples were collected at the same time from all subjects. Levels of prohepcidin and hepcidin were measured by ELISA. The presence of hepcidin in salivary glands was assessed by immunohistochemistry. ResultsHepcidin was localized in the striated ducts of the sublingual and parotid glands. Saliva prohepcidin and hepcidin levels were correlated with blood levels. Saliva prohepcidin levels were found to be lower in RAS patients than in BD patients and healthy controls (P<0.001 and P=0.007 respectively). In addition, RAS patients had lower saliva hepcidin levels than did the control group (P=0.03). ConclusionsThe lower serum and saliva prohepcidin and hepcidin concentrations found in RAS and BD patients indicate that hepcidin may be involved in the aetiopathogenesis of these diseases. Because it can be obtained non-invasively and easily, saliva may provide a useful alternative to serum in quantifying prohepcidin and hepcidin concentrations.
Keywords: Streptococcus-Sanguis; Saliva